Coordination in a Single-Retailer Two-Supplier Supply Chain under Random Demand and Random Supply with Disruption - Fei Hu; Cheng-Chew Lim; Zudi Lu; Xiaochen Sun (Discrete Dynamics in Nature and Society)
This paper studies the coordination issue of a supply chain consisting of one retailer and two suppliers, a main supplier and a backup supplier. The main supplier’s yield is subject to disruption and the retailer faces a random demand. We determine the retailer’s optimal ordering policy and the main supplier’s production quantity that maximize expected profit of the centralized supply chain. We also analyze the decentralized scenario, and a combination of overproduction risk sharing and buy-back contracts with a side payment from/to the backup supplier is provided to coordinate the supply chain. Numerical examples are given to gain some qualitative insights.